BACTERIAL FLORA OF FRESH AÂ·ND ICED INDIAN MACKEREL (RASTRELLIGER KANAGURTAJ AND ITS RESPONSE TO CHLORTETRACYCLINE (CTC) TREATMENT - SURENDRAN, P K; IYER, K MAHADEVA (Fishery Technology, 2017)
Quantitative and qualitative studies on the bacterial flora of fresh Indian mackerel ( Rastrelliger kanagurta) have been made. The total native flora as well as 5 ppm. CTC insensitive flora of the fish showed variations with season. About 90 % of the fresh fish flora was sensitive to 5 ppm. CTC. The natural flora of the fresh fish consisted of Vibrios, Pseudomonas, Achromobacter, Flavobacterium, Corynebacteria, Micrococci, Bacillus and yeasts. In the CTC insensitive flora, Vibrios predominated followed by yeasts. The selection of bacterial genera during storage of the fish in ice and in 5 ppm. CTC incorporated ice has also been investigated. At the time of spoilage, Pseudomonas were found to be the dominant flora of the fish stored in both types of ice.